Counterfactual Analyses of Oil Price Shocks using a World Model - Ray Barrell; Knut A. Magnussen (Statistics Norway, Research Department, 1996)
Oil price shocks have played a dominant role in the macroeconomic development of the world economy over the last twenty five years. In this paper a large, estimated, macro-economic world model with time varying trade weights, monetary and fiscal policy rules and explicit modelling of the behaviour of the OPEC countries is used for counterfactual analyses of oil price shocks. An alternative history with constant real oil prices is developed, showing that the recessions in the OECD area in 1974/75 and in 1980 would have been milder without the preceding oil price hike, while the 1982 recession seems unrelated to oil prices. A separate simulation indicates that the oil price drop in 1985/86 prevented a small recession from developing. The paper also shows that macroeconomic oil price effects vary considerably between the US, Germany and Japan according to the degree of oil dependence, trade with OPEC and the working of domestic labour markets. In particular there are notable differences in inflationary effects in Germany and the US. Results are tested against alternative specifications of monetary and fiscal policy rules.
Keywords: Q43; E37; E61; 330; Oil price shocks; Macro-economic model; Policy rules